Pengaruh Aksesibilitas Bank Emok Terhadap Minat Masyarakat Dalam Pemanfaatan Jasa Koperasi Syariah (Studi pada Koperasi Syariah Masjid Besar Kecamatan Ganeas Kabupaten Sumedang): - - HAMID, ABDUL HAMID; Maulin, Merry; Syaripudin , Enceng Iip; Konkon Furkony , Deni (STAI Al Musaddadiyah Garut, 2022)
This study aims to examine the effect of Bank Emok accessibility on public interest in utilizing sharia cooperative services. This study was conducted using a quantitative approach. The number of samples used in this study was 30 respondents taken from Bank Emok customers using purposive sampling techniques. The data sources obtained in this study are primary and secondary data sources. The results of this study show that Bank Emok's accessibility variable has a linear relationship with the variable of public interest in the use of sharia cooperative services. Based on the T test that has been carried out, it shows that the accessibility variable of Bank Emok has a significant influence on the variable of public interest in the use of Islamic bank services. Meanwhile, based on the R square test that has been carried out, it shows that Bank Emok's accessibility variable has an influence of 68.4% on the variable of public interest. Keywords: Accessibility, Bank emok, Interest, Sharia Cooperative.